Penerapan Standar Operasional Prosedur (SOP) dalam Produksi Eco Enzyme sebagai Upaya Penguatan Kapasitas Mitra Pengelola Sampah - Rivan Muhfidin; Sely Novita Sari; Ratna Kartikasari; Yulius Wijanarko; Khairul Mahbubi (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
The Mukti Jaya Waste Management Group faced irregularities in eco enzyme production, resulting in low product quality and inefficiency. This community engagement aimed to enhance the group's technical and managerial capacity through the implementation of Standard Operating Procedures (SOPs). The methods included initial observation, participatory SOP development, hands-on technical training, and implementation mentoring. Results showed an increase in production volume from 12 to 20 liters per batch, a 40% improvement in time efficiency, and a rise in active member participation from 44.4% to 84.4%. Understanding of standardized procedures also improved from a score of 2.7 to 4.4. Evaluations using questionnaires and field observations confirmed enhanced technical and organizational capabilities. Additional impacts included the adoption of production and financial recording systems, the development of a collective work culture, and increased environmental awareness. SOPs proved to be not only a technical guide but also a community empowerment tool promoting efficiency, self-reliance, and sustainability in organic waste management.